Upaya Meminimalisir Kecelakaan Kerja di Area Penambangan PT. Adaro Services Job Site Binungan, Berau Provinsi Kalimantan Timur - Hafidz Haidi; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Unsafe conditions and unsafe actions at PT Adaro Service are the main causes of accidents that cause loss and loss to humans and companies, damage to equipment, disrupt production and others. The number of work accidents has increased dramatically at the beginning of 2018, there are still employees who ignore the use of personal protective equipment, and there are still hazards found in the work environment. This problem aims to reveal the work location that has the highest potential hazard in the mining area, the potential hazards that exist in the work environment and reveal what actions should be taken to prevent work accidents, and reveal work accident statistics. The implementation of K3 in companies is still not optimal, this is evident in the increasing number of work accidents in early 2018. The danger cannot be completely eliminated, but can be minimized. this study uses the Job Safety Analysis and Job Hazard Analysis methods to identify and analyze hazards on a job. after identifying the danger, so that to control it will be given a recommendation. Not only do hazard identification activities, but this research will also make several Job Safety Analysis and Job Hazard Analysis. By analyzing these two requirements, it is expected that the Job Safety Analysis and Job Hazard Analysis will facilitate the establishment of an occupational health and safety management system.Keywords: Production, Safety, Danger, Job Hazard Analysis, Job Safety Analysis.